ASSESSING THE IMPACT OF THE SCIENCEREADY PREPARATORY SHORT COURSE ON STUDENT ACADEMIC PERFORMANCE: Received: 23rd March 2023; Revised: 25th July 2023, 26th July 2023, 31st July 2023; Accepted: 02nd August 2023 - Erin Lousberg,; Rajini Lagiseti,; Jyothi Thalluri, (PUPIL: International Journal of Teaching, Education and Learning, 2023)
Starting university can be a daunting experience representing a big adjustment for first year students. Facilitating a smooth transition to university sets students up for successful degree completion; however, if students struggle or become disengaged, they can underperform or drop out completely. An early support system, the 'ScienceReady' short course has been designed to assist with the transition to university study for nursing and midwifery students. It has been designed to provide essential academic skills and foundational science knowledge, reduce anxiety, and assist in the formation of early friendship groups, with the overall aim to improve student success. As well as improving background knowledge, the course also allows students to visit laboratories, meet staff and interact with their peers. Despite its scope, we knew little about the impact of attending ScienceReady on later academic outcomes. This study assessed the impact of ScienceReady attendance on first-year academic success, providing evidence for the importance of early support systems in tertiary success.